L’urbanistica riconoscerà mai il ruolo dei sistemi informativi territoriali? - Salvemini, Mauro (GEOmedia, 2012)
It is discussed the role of GI in contemporary city planning considering three 2012 May events.REAL CORP 2012 in Schwechat which of-fered the possibility to collectively discuss a wide range of topics in different panel groups and workshops about "RE-MIXING THE CITY” which is a challenge to manage and re-combine the elements which make our modern cities in order to better respond to change. INPUT 2012 which in Cagliari was discuss-ing how new technologies play a prominent role in the innovation of planning theory and practice, as they affect every phase of the process: knowledge building, preliminary studies, design, decision, implementation, and monitoring.The kick off of the EC co-funded project Plan-4Business which aims to develop a platform that can serve users a full catalogue of plan-ning data such as transport infrastructure, re-gional plans, urban plans and zoning plans.